Antiepileptic drug withdrawal - Jędrzejczak, Joanna (Przewodnik Lekarza/Guide for GPs, 2007)
Of patients with epilepsy 60-70% achieve control with antiepileptic treatment. In some patients remission can occur, and physicians treating epilepsy are often asked to predict prognosis and make decisions about withdrawing treatment. Identifying patients from whom treatment can be withdrawn successfully would be beneficial on many levels, but selecting patients may be difficult. Several published studies show variable rates of success with relapse rates ranging from 12 to 63%. Several prognostic factors can help identify patients in whom antiepileptic drug withdrawal can be done. The aim of this article is to present general guidelines for antiepileptic drug withdrawal.